Influence of soaking temperature and time on the kinetics of water absorption and pasting properties of glutinous rice - Pattharasuda Hanucharoenkul; Chuthawan Theerathanan; Rungnaphar Pongsawatmanit (Agriculture and Natural Resources, 2021)
Soaking process is an important pretreatment step affecting on water absorption and gelatinization of rice starch. Glutinous rice (RD6 variety), with whole and broken kernels, was used to investigate the effect of soaking condition on the kinetics of water absorption. Both kernel types were soaked in water (rice kernel: water = 1:1.5) at 30, 40 and 50°C and sampled out at selected soaking times (0.25, 0.5, 0.75, 1, 1.5, 2, 2.5, 3, 5 and 8 h). The water absorption of the broken kernel was higher than that of the whole kernel at the same soaking time resulted from the greater surface area for water penetration. The sorption process was described using Peleg model and revealed that mass transfer rate of broken kernel increased with increasing temperature. The obtained water absorption capacity of broken kernel was higher than that of whole sample. Temperature dependence of rate constant from broken kernel was higher than that of whole kernel according to Arrhenius equation. The pasting properties of soaked grains at 30°C were evaluated using a rapid visco-analyzer. Peak and final viscosities of all soaked rice kernel were higher than those of the kernel without soaking. The final viscosity increased with increasing moisture content in the rice kernel. The information gained in this study could be further applied for rice-based product in food industry.